Optical characterization and redescription of the South Pacific firefly Bourgeoisia hypocrita Olivier (Coleoptera: Lampyridae: Luciolinae) - Deheyn, Dimitri D.; Ballantyne, Lesley A. (Zootaxa, 2009)
Bourgeoisia hypocrita Olivier is an atypical species of firefly where males lack light organs in ventrite 7 and have reduced light organs in ventrite 6 and may not produce light at all, while females are flightless and produce a long-lasting glow (up to tens of seconds). Here, photobiology of females is described for the first time. Colour of produced bioluminescence ranges in the green to yellow/green. Spectrum is unimodal peaking at 575–595 nm but more complex than other fireflies in having two shoulders at 545–550 nm and 600–610 nm. A taxonomic re-examination of the species based on recent collections and type material shows that larvae and adults exhibit a peculiar dark pigmentation. Fluorescence and absorbance of adult extracts indicate this pigmentation could be involved in UV protection, in addition to possibly serving as cryptic camouflage. Fluorescence and absorbance of eggs, which have a light gold colour, indicate the luminous compound could be used as an antioxidant during this early life stage. Overall, the signal of bioluminescence shows characteristics of a basal system of flash communication in B. hypocrita, which associates light production not only to visual communication but also possibly to UV and/or free radicals protective mechanisms.